Morphological characterization of some representative species of the genus Loxoblemmus (Orthoptera: Gryllidae; Gryllinae; Gryllini) from India - Mal, Jhabar; Nagar, Rajendra; Swaminathan, R. (Zootaxa, 2015)
Morphological characterization of some common species of the genus Loxoblemmus (Gryllidae: Gryllinae) from India is presented. In all, 5 species were identified that included two, Loxoblemmus equestris Saussure and Loxoblemmus haani Saussure, from the sub-humid regions of Rajasthan (South West India) and Madhya Pradesh (Central India); while three species, Loxoblemmus taicoun Saussure, Loxoblemmus jacobsoni Chopard and Loxoblemmus intermedius Chopard from the humid hilly regions of Meghalaya and Assam (North East India). Of the 5 reported species, based on the comparative linear measurements, L. haani is relatively larger than the other species encountered.